Critical discourse analysis on President Rodrigo Duterte's remarks on women - Ompong, Lyka Mae L.; Comidoy, Merle Dawn S. (2019)
Critical Discourse Analysis is known as an approach that is based on the union of language studies and social theory. It can be applied to investigate how social power is misused and how text and talk represent, reproduce and resist dominance and inequality in the social and political context. It is often applied to analyze political discourse including public speeches, in which the speaker uses the language to serve and normalize his ideology to his audience. Language is one of the most powerful means through which sexism and gender discrimination is penetrated and reproduced. Duterte became famous both in international and national sphere because of his sexism in language. Sexism, in language contribute to the existing gender discrimination on women. In order to reduce gender bias, it is necessary to change people?s linguistic habits by making them aware of the detrimental effects of sexism in language. it is also important to make people or the audience realize that these sexist remarks are not funny which only normalize gender discrimination. This paper is based on Critical Discourse Analysis and Butler?s Gender Performativity Theory to analyze Rodrigo Duterte?s remarks on women. This research aims to have a better understanding on the purpose of these political speeches by examining Duterte?s remarks on women found in his speeches from June 2016 to December 2018. In order to have an intensive discussion, the researcher studied the micro and macrostructures of the remarks. In the microstructure analysis, the researcher studied the syntactic, stylistic, rhetoric, semantic
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019